Validation of L2 grit among Chinese EFL high school students and its enduring effect on achievements: A bifactor model approach - Liu, Eerdemutu; Wang, Junju; Bai, Sachurina (Frontiers in Psychology, 2022)
The current study seeks to validate L2 grit measure among 637 Chinese senior middle school students using a bifactor modelling approach. To do so, we first assessed and compared four alternative measurement models including CFA, bifactor CFA, ESEM, and bifactor ESEM models. Among these models, CFA exhibited the poorest fit to the data collected from the sample. ESEM showed partial fit to the data with a slightly lower factor correlation between two components of L2 grit (i.e., perseverance of effort and consistency of interest) than CFA. Two bifactor models (bifactor CFA and bifactor ESEM) demonstrated excellent fits to the data. The more parsimonious bifactor CFA model was selected as the optimal one. Based on the bifactor CFA model, we confirmed measurement invariance across gender and predictive validity of L2 grit on subsequent language achievements. Based on these findings, methodological and pedagogical implications were discussed.